EFFECT OF NASYA KARMA WITH KARPASHASTHADI TAILAM IN ARDITA (BELL’S PALSY): A CASE STUDY - Dipanjan Jana; Behra Manoj Kumar; Mandal Nisith Kumar; Swarup De (International Journal of Applied Ayurved Research, 2018)
Nasya karma is one of the most important Panchakarma for the Urdhwajatrugata roga. As Ardita comes under urdhwajatrugata roga, Nasya karma is the choice of treatment. The Ardita comes under Vata vyadhi and therefore snehana is considered as the best therapeutic option. The sneha can be used in various forms depending on the condition, so sneha can also be used in the form of Nasya in Ardita, because Nasya Karma is believed to have a major role in the treatment of Ardita. Objective was to observe the efficacy of Karpashastadi tailam nasya in the management of Ardita. A 26 year old female patient presenting with sudden onset of asymmetry of face, mild pain and loss of movement on left side of face, difficulty in chewing and improper close of right eye come to OPD of Raghunath Ayurveda Mahavidyalaya and Hospital. History and examinations leads to the diagnosis of Ardita (Bell’s palsy). So patient was treated according to principal of Ardita chikitsa i.e, Nasya with Karpashastadi tailam. A remarkable effect was observed in terms of clinical features. Nasya karma has been found to be potentially effective in recovery from Ardita in that case.